2011
DOI: 10.1542/peds.2011-1869
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Biliary Atresia Have Elevated Direct/Conjugated Bilirubin Levels Shortly After Birth

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Infants with biliary atresia (BA) have better outcomes if detected and treated early, typically before 8 weeks of age. Making an early diagnosis is difficult, however, because newborns appear healthy and start developing disease at an unknown time. WHAT THIS STUDY ADDS:Patients with BA have elevated direct/ conjugated bilirubin (DB/CB) levels at birth. BA could be detected earlier if: (1) all newborns have DB/CB levels measured, including those not jaundiced; and (2) all elevated D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
134
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 162 publications
(147 citation statements)
references
References 25 publications
8
134
1
Order By: Relevance
“…In our experience, infants with BA have newborn direct or conjugated bilirubin concentrations that exceed their birth hospital's derived reference interval (1 ). In contrast, this infant had a reported "Neonatal Dbil" concentration of 0.5 mg/dL on DoL 1, which was within the birth hospital's reported reference interval of 0.0 -0.6 mg/dL.…”
Section: Case Descriptionmentioning
confidence: 59%
See 1 more Smart Citation
“…In our experience, infants with BA have newborn direct or conjugated bilirubin concentrations that exceed their birth hospital's derived reference interval (1 ). In contrast, this infant had a reported "Neonatal Dbil" concentration of 0.5 mg/dL on DoL 1, which was within the birth hospital's reported reference interval of 0.0 -0.6 mg/dL.…”
Section: Case Descriptionmentioning
confidence: 59%
“…For example, the main message of this report-the incorrect interpretation of "Neonatal Dbil" delaying the diagnosis of BAreinforces the conclusions of a recent landmark study published by the same group, which is casually referenced in the context of the case presentation. This notable study (1 ) documented that direct-reacting or conjugated bilirubin is increased as early as 24 -48 h after birth in most children with the perinatal form of BA, which accounts for 70%-85% of BA in infants. These findings raise the possibility that measurements of conjugated or direct bilirubin could be used as a screening tool for early detection…”
Section: Authors' Disclosures or Potential Conflicts Of Interest: No mentioning
confidence: 84%
“…At present, the analysis of dried blood spots derived from the standard newborn screening card has not proven useful for biliary atresia, primarily because of the lack of a diagnostic metabolite. However, recent data suggests that measurement of direct bilirubin levels within the first 2 days of life could be used as a screening tool [6,7,13]. …”
Section: Biliary Atresia Epidemiology and Salient Clinical Conceptsmentioning
confidence: 99%
“…This paper is focused upon highlighting the current state of discovery and knowledge regarding genes that may confer susceptibility to biliary atresia or modulate outcomes among infants after HPE. It is likely that a deeper understanding of the genetic profile of infants with biliary atresia will provide clinically substantive insights into the etiology and severity of the disease, and enable the development of more precise diagnostic methods and rational therapeutic targets to improve outcomes [2,7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a recent study showed that over half of patients with biliary atresia have elevated direct/conjugated bilirubin levels shortly after birth. 5 The cause of biliary atresia is unknown. Several mechanisms have been proposed to account for the progressive obliteration of the extrahepatic biliary tree.…”
mentioning
confidence: 99%